Rising Above the Gathering Storm, Revisited: Rapidly Approaching Category 5 - National Academy of Sciences; National Academy of Engineering; Institute of Medicine (The National Academies Press, 2010)
In the face of so many daunting near-term challenges, U.S. government and industry are letting the crucial strategic issues of U.S. competitiveness slip below the surface. Five years ago, the National Academies prepared Rising Above the Gathering Storm, a book that cautioned: "Without a renewed effort to bolster the foundations of our competitiveness, we can expect to lose our privileged position." Since that time we find ourselves in a country where much has changed--and a great deal has not changed. So where does America stand relative to its position of five years ago when the Gathering Storm book was prepared? The unanimous view of the authors is that our nation's outlook has worsened. The present volume, Rising Above the Gathering Storm, Revisited, explores the tipping point America now faces. Addressing America's competitiveness challenge will require many years if not decades; however, the requisite federal funding of much of that effort is about to terminate. Rising Above the Gathering Storm, Revisited provides a snapshot of the work of the government and the private sector in the past five years, analyzing how the original recommendations have or have not been acted upon, what consequences this may have on future competitiveness, and priorities going forward. In addition, readers will find a series of thought- and discussion-provoking factoids--many of them alarming--about the state of science and innovation in America. Rising Above the Gathering Storm, Revisited is a wake-up call. To reverse the foreboding outlook will require a sustained commitment by both individual citizens and government officials--at all levels. This book, together with the original Gathering Storm volume, provides the roadmap to meet that goal. While this book is essential for policy makers, anyone concerned with the future of innovation, competitiveness, and the standard of living in the United States will find this book an ideal tool for engaging their government representatives, peers, and community about this momentous issue.
Keywords: Policy for Science and Technology; Education; Engineering and Technology; Industry and Labor

Rising Above the Gathering Storm: Developing Regional Innovation Environments: Summary of a Workshop - National Academy of Sciences; National Academy of Engineering; Institute of Medicine (The National Academies Press, 2012)
In October 2005, the National Academy of Sciences, National Academy of Engineering, and Institute of Medicine released a policy report that served as a call to action. The report, Rising Above the Gathering Storm: Energizing and Employing America for a Brighter Economic Future observed that "the scientific and technological building blocks critical to the United States economic leadership are eroding at a time when many other nations are gathering strength." The report laid out 20 recommendations in four broad areas - K-12 education, science and engineering research, higher education, and economic and technology policy - and warned that a failure to take action could have dire economic consequences. Rising Above the Gathering Storm sparked intense discussion among policy makers, industrial leaders, and the general public. Five years after the release of the Gathering Storm report, a second report, Rising Above the Gathering Storm, Revisited: Rapidly Approaching Category 5, assessed changes in America's competitive posture. This report concluded that "our nation's outlook has not improved, but rather has worsened" since the Gathering Storm report was released. The report noted examples of other nations that have upgraded their investments in education, technological infrastructure, and innovation systems to a greater extent than has the United States. The ability of the states to drive innovation was the impetus behind a major workshop held in Madison, Wisconsin, on September 20-22, 2011. Titled "Rising Above the Gathering Storm: Developing Regional Innovation Environments," the workshop brought together leaders in education, government, economic development, and industrial innovation to discuss state and regional initiatives to boost competitiveness through science, technology, and innovation. The conference was organized around four major themes: - Revitalizing K-12 Science and Mathematics Education - Strengthening Undergraduate Education in Science and Engineering - Building Effective Partnerships Among Governments, Universities, Companies, and Other Stakeholders - Fostering Regional Technology Development and Entrepreneurship Rising Above the Gathering Storm: Developing Regional Innovation Environments: A Workshop Summary gives an overview of the presentations, observations, and recommendations made during the workshop.
Keywords: Engineering and Technology; Education

Rising Above the Gathering Storm, Revisited: Rapidly Approaching Category 5: Condensed Version - 2005 "Rising Above the Gathering Storm" Committee (The National Academies Press, 2011)
In 2005 the National Academies released Rising Above the Gathering Storm, a book focused on the ability of all Americans to compete for quality jobs in the evolving global economy. Rising Above the Gathering Storm concluded that a primary driver of the future economy and concomitant creation of jobs in the 21st century will be innovation, largely derived from advances in science and engineering. It proposed four overarching recommendations, underpinned by 20 specific implementing actions. The America COMPETES Act approved many of the recommendations set forth in Rising Above the Gathering Storm. In 2010, the National Academies released Rising Above the Gathering Storm, Revisited, an updated volume that outlines the work of the government and the private sector in the past five years. This volume also presents a series of thought-provoking factoids about the state of science and innovation in America. It asserts that the 20 actions previously endorsed should be fully implemented. This report is a condensed version of Rising Above the Gathering Storm, Revisited.
Keywords: Policy for Science and Technology

Rising Above the Gathering Storm: Energizing and Employing America for a Brighter Economic Future - National Academy of Sciences; National Academy of Engineering; Institute of Medicine (The National Academies Press, 2007)
In a world where advanced knowledge is widespread and low-cost labor is readily available, U.S. advantages in the marketplace and in science and technology have begun to erode. A comprehensive and coordinated federal effort is urgently needed to bolster U.S. competitiveness and pre-eminence in these areas. This congressionally requested report by a pre-eminent committee makes four recommendations along with 20 implementation actions that federal policy-makers should take to create high-quality jobs and focus new science and technology efforts on meeting the nation's needs, especially in the area of clean, affordable energy: 1) Increase America's talent pool by vastly improving K-12 mathematics and science education; 2) Sustain and strengthen the nation's commitment to long-term basic research; 3) Develop, recruit, and retain top students, scientists, and engineers from both the U.S. and abroad; and 4) Ensure that the United States is the premier place in the world for innovation. Some actions will involve changing existing laws, while others will require financial support that would come from reallocating existing budgets or increasing them. Rising Above the Gathering Storm will be of great interest to federal and state government agencies, educators and schools, public decision makers, research sponsors, regulatory analysts, and scholars.
Keywords: Industry and Labor; Education; Engineering and Technology; Policy for Science and Technology

Rising Above the Gathering Storm Two Years Later: Accelerating Progress Toward a Brighter Economic Future: Summary of a Convocation - National Academy of Sciences; National Academy of Engineering; Institute of Medicine (The National Academies Press, 2009)
Rising Above the Gathering Storm Two Years Later: Accelerating Progress Toward a Brighter Economic Future summarizes a convocation held in April 2008 to commemorate the release of the original Gathering Storm report. The convocation featured participation by Members of Congress, Cabinet Secretaries, leaders from industry and academia, and other experts. The discussions reviewed progress made thus far in implementing the Gathering Storm recommendations to strengthen K-12 education in math and science, research, higher education, and the environment for innovation. Participants also noted that much additional work is needed to ensure that America remains a leader in science and engineering in the long term.
Keywords: Industry and Labor; Education; Engineering and Technology; Policy for Science and Technology

Imagining the Future of Undergraduate STEM Education: Proceedings of a Virtual Symposium - National Academy of Engineering; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2022)
In November 2020, the National Academies of Sciences, Engineering, and Medicine convened a multi-day virtual symposium on imaging the future of undergraduate STEM education. Speakers and participants pondered the future and the past and shared their goals, priorities, and dreams for improving undergraduate STEM education. Expert speakers presented information about today's students and approaches to undergraduate STEM education, as well as the history of transformation in higher education. Thoughtful discussions explored ideas for the future, how student-centered learning experiences could be created, and what issues to consider to facilitate a successful transformation. This publication summarizes the presentation and discussion of the symposium.
Keywords: Education

An Interim Report on Assuring DoD a Strong Science, Technology, Engineering, and Mathematics (STEM) Workforce - National Academy of Engineering; National Research Council (The National Academies Press, 2012)
An Interim Report on Assuring DoD a Strong Science, Technology, Engineering, and Mathematics (STEM) Workforce is a report on the science, technology, mathematics, and engineering (STEM) workforce of the Department of Defense (DOD) and the U.S. defense industrial base is part of an 18-month study to assess the STEM capabilities that the DOD will need in order to meet its goals, objectives, and priorities. This study also assesses whether the current DOD workforce and strategy will meet those needs; and indentifies and evaluates options and recommends strategies that the department could use to help meet its future STEM needs. This study was undertaken by the National Academy of Engineering and the National Research Council. This report was issued for the purpose of assisting Assistant Secretary of Defense for Research and Engineering with its fiscal year 2012 planning process and with laying the groundwork for future years. Earlier in the project, the Committee on Science, Technology, Engineering, and Mathematics Workforce Needs for the U.S. Department of Defense and the U.S. Defense Industrial Base convened a workshop on August 1 and 2, 2011, in Rosslyn, Virginia. This workshop met for the purpose of gathering a broad range of views from the public sector and the private sector. This includes major defense contractors, and from nongovernmental organizations (NGOs), all of which are stakeholders in the future STEM workforce. At the conclusion of this study, a final report will be released.
Keywords: Industry and Labor; Education

STEM Integration in K-12 Education: Status, Prospects, and an Agenda for Research - National Academy of Engineering; National Research Council (The National Academies Press, 2014)
STEM Integration in K-12 Education examines current efforts to connect the STEM disciplines in K-12 education. This report identifies and characterizes existing approaches to integrated STEM education, both in formal and after- and out-of-school settings. The report reviews the evidence for the impact of integrated approaches on various student outcomes, and it proposes a set of priority research questions to advance the understanding of integrated STEM education. STEM Integration in K-12 Education proposes a framework to provide a common perspective and vocabulary for researchers, practitioners, and others to identify, discuss, and investigate specific integrated STEM initiatives within the K-12 education system of the United States. STEM Integration in K-12 Education makes recommendations for designers of integrated STEM experiences, assessment developers, and researchers to design and document effective integrated STEM education. This report will help to further their work and improve the chances that some forms of integrated STEM education will make a positive difference in student learning and interest and other valued outcomes.
Keywords: Education; Engineering and Technology

Community Colleges in the Evolving STEM Education Landscape: Summary of a Summit - National Academy of Engineering; National Research Council (The National Academies Press, 2012)
The National Research Council (NRC) and National Academy of Engineering (NAE) have released a new report, Community Colleges in the Evolving STEM Education Landscape: Summary of a Summit. Based on a national summit that was supported by the National Science Foundation and organized by the NRC and the NAE, the report highlights the importance of community colleges, especially in emerging areas of STEM (Sciene, Technology, Engineering, and Mathematics) and preparation of the STEM workforce. Community colleges are also essential in accommodating growing numbers of students and in retraining displaced workers in skills needed in the new economy. Community Colleges in the Evolving STEM Education Landscape: Summary of a Summit looks at the changing and evolving relationships between community colleges and four-year institutions, with a focus on partnerships and articulation processes that can facilitate student success in STEM; expanding participation of students from historically underrepresented populations in undergraduate STEM education; and how subjects, such as mathematics, can serve as gateways or barriers to college completion.
Keywords: Education

Assuring the U.S. Department of Defense a Strong Science, Technology, Engineering, and Mathematics (STEM) Workforce - National Academy of Engineering; National Research Council (The National Academies Press, 2012)
The ability of the nation's military to prevail during future conflicts, and to fulfill its humanitarian and other missions, depends on continued advances in the nation's technology base. A workforce with robust Science, Technology, Engineering and Mathematics (STEM) capabilities is critical to sustaining U.S. preeminence. Today, however, the STEM activities of the Department of Defense (DOD) are a small and diminishing part of the nation's overall science and engineering enterprise. Assuring the U.S. Department of Defense a Strong Science, Technology, Engineering, and Mathematics (STEM) Workforce presents five principal recommendations for attracting, retaining, and managing highly qualified STEM talent within the department based on an examination of the current STEM workforce of DOD and the defense industrial base. As outlined in the report, DOD should focus its investments to ensure that STEM competencies in all potentially critical, emerging topical areas are maintained at least at a basic level within the department and its industrial and university bases.
Keywords: Education; Industry and Labor; Conflict and Security Issues

Report of a Workshop on Science, Technology, Engineering, and Mathematics (STEM) Workforce Needs for the U.S. Department of Defense and the U.S. Defense Industrial Base - National Academy of Engineering; National Research Council (The National Academies Press, 2012)
Report of a Workshop on Science, Technology, Engineering, and Mathematics (STEM) Workforce Needs for the U.S. Department of Defense and the U.S. Defense Industrial Base is the summary of a workshop held August 11, 2011, as part of an 18-month study of the issue. This book assesses the STEM capabilities that the Department of Defense (DOD) needs in order to meet its goals, objectives, and priorities; to assess whether the current DOD workforce and strategy will meet those needs; and to identify and evaluate options and recommend strategies that the department could use to help meet its future STEM needs.
Keywords: Engineering and Technology; Industry and Labor

Barriers and Opportunities for 2-Year and 4-Year STEM Degrees: Systemic Change to Support Students' Diverse Pathways - National Academy of Engineering; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2016)
Nearly 40 percent of the students entering 2- and 4-year postsecondary institutions indicated their intention to major in science, technology, engineering, and mathematics (STEM) in 2012. But the barriers to students realizing their ambitions are reflected in the fact that about half of those with the intention to earn a STEM bachelor's degree and more than two-thirds intending to earn a STEM associate's degree fail to earn these degrees 4 to 6 years after their initial enrollment. Many of those who do obtain a degree take longer than the advertised length of the programs, thus raising the cost of their education. Are the STEM educational pathways any less efficient than for other fields of study? How might the losses be "stemmed" and greater efficiencies realized? These questions and others are at the heart of this study. Barriers and Opportunities for 2-Year and 4-Year STEM Degrees reviews research on the roles that people, processes, and institutions play in 2-and 4-year STEM degree production. This study pays special attention to the factors that influence students' decisions to enter, stay in, or leave STEM majors—quality of instruction, grading policies, course sequences, undergraduate learning environments, student supports, co-curricular activities, students' general academic preparedness and competence in science, family background, and governmental and institutional policies that affect STEM educational pathways. Because many students do not take the traditional 4-year path to a STEM undergraduate degree, Barriers and Opportunities describes several other common pathways and also reviews what happens to those who do not complete the journey to a degree. This book describes the major changes in student demographics; how students, view, value, and utilize programs of higher education; and how institutions can adapt to support successful student outcomes. In doing so, Barriers and Opportunities questions whether definitions and characteristics of what constitutes success in STEM should change. As this book explores these issues, it identifies where further research is needed to build a system that works for all students who aspire to STEM degrees. The conclusions of this report lay out the steps that faculty, STEM departments, colleges and universities, professional societies, and others can take to improve STEM education for all students interested in a STEM degree.
Keywords: Education

Is America Falling Off the Flat Earth? - National Academy of Sciences; National Academy of Engineering; Institute of Medicine (The National Academies Press, 2007)
The aviation and telecommunication revolutions have conspired to make distance increasingly irrelevant. An important consequence of this is that US citizens, accustomed to competing with their neighbors for jobs, now must compete with candidates from all around the world. These candidates are numerous, highly motivated, increasingly well educated, and willing to work for a fraction of the compensation traditionally expected by US workers. If the United States is to offset the latter disadvantage and provide its citizens with the opportunity for high-quality jobs, it will require the nation to excel at innovation--that is, to be first to market new products and services based on new knowledge and the ability to apply that knowledge. This capacity to discover, create and market will continue to be heavily dependent on the nation's prowess in science and technology. Indicators of trends in these fields are, at best, highly disconcerting. While many factors warrant urgent attention, the two most critical are these: (1) America must repair its failing K-12 educational system, particularly in mathematics and science, in part by providing more teachers qualified to teach those subjects, and (2) the federal government must markedly increase its investment in basic research, that is, in the creation of new knowledge. Only by providing leading-edge human capital and knowledge capital can America continue to maintain a high standard of living--including providing national security--for its citizens.
Keywords: Industry and Labor; Computers and Information Technology; Education; Engineering and Technology; Policy for Science and Technology

Extraordinary Engineering Impacts on Society: Proceedings of a Symposium - National Academy of Engineering; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2023)
On August 18-19, 2022, the National Academy of Engineering (NAE) held a symposium to explore how support of fundamental engineering and engineering education research by the National Science Foundation (NSF) has led to positive societal and economic impacts. The symposium - which was sponsored by the NSF Directorate for Engineering - was held to provide input to the NAE Committee on Extraordinary Engineering Impacts on Society as part of a larger effort to develop clear, compelling narratives for the public about the sources and effects of engineering innovations. Speakers at the symposium shared their personal stories and provided insights on how engineers influence not only technology and the national infrastructure but the economy, population health, manufacturing, disaster resilience, and many other aspects of daily life. This publication summarizes the presentations and discussion of the symposium.
Keywords: Engineering and Technology

Surmounting the Barriers: Ethnic Diversity in Engineering Education: Summary of a Workshop - National Academy of Engineering (The National Academies Press, 2014)
Surmounting the Barriers: Ethnic Diversity in Engineering Education is the summary of a workshop held in September 2013 to take a fresh look at the impediments to greater diversification in engineering education. The workshop brought together educators in engineering from two- and four-year colleges and staff members from the three sponsoring organizations: the National Science Foundation, the National Academy of Engineering and the American Society for Engineering Education. While the goal of diversifying engineering education has long been recognized, studied, and subjected to attempted interventions, progress has been fitful and slow. This report discusses reasons why past recommendations to improve diversity had not been adopted in full or in part. Surmounting the Barriers identifies a series of key impediments, including a lack of incentives for faculty and institutions; inadequate or only short-term financial support; an unsupportive institutional and faculty culture and environment; a lack of institutional and constituent engagement; and inadequate assessments, metrics, and data tracking. The report also shares success stories about instances where barriers to diversity have been identified and surmounted, and the resources that could enable real solutions to implement steps toward progress.
Keywords: Engineering and Technology; Education

Macondo Well Deepwater Horizon Blowout: Lessons for Improving Offshore Drilling Safety - National Academy of Engineering; National Research Council (The National Academies Press, 2012)
The blowout of the Macondo well on April 20, 2010, led to enormous consequences for the individuals involved in the drilling operations, and for their families. Eleven workers on the Deepwater Horizon drilling rig lost their lives and 16 others were seriously injured. There were also enormous consequences for the companies involved in the drilling operations, to the Gulf of Mexico environment, and to the economy of the region and beyond. The flow continued for nearly 3 months before the well could be completely killed, during which time, nearly 5 million barrels of oil spilled into the gulf. Macondo Well-Deepwater Horizon Blowout examines the causes of the blowout and provides a series of recommendations, for both the oil and gas industry and government regulators, intended to reduce the likelihood and impact of any future losses of well control during offshore drilling. According to this report, companies involved in offshore drilling should take a "system safety" approach to anticipating and managing possible dangers at every level of operation -- from ensuring the integrity of wells to designing blowout preventers that function under all foreseeable conditions-- in order to reduce the risk of another accident as catastrophic as the Deepwater Horizon explosion and oil spill. In addition, an enhanced regulatory approach should combine strong industry safety goals with mandatory oversight at critical points during drilling operations. Macondo Well-Deepwater Horizon Blowout discusses ultimate responsibility and accountability for well integrity and safety of offshore equipment, formal system safety education and training of personnel engaged in offshore drilling, and guidelines that should be established so that well designs incorporate protection against the various credible risks associated with the drilling and abandonment process. This book will be of interest to professionals in the oil and gas industry, government decision makers, environmental advocacy groups, and others who seek an understanding of the processes involved in order to ensure safety in undertakings of this nature.
Keywords: Environment and Environmental Studies

Advancing Diversity in the US Industrial Science and Engineering Workforce: Summary of a Workshop - National Academy of Engineering (The National Academies Press, 2014)
Thousands of gifted individuals, including women and underrepresented minorities, remain a disproportionally small fraction of those in science, technology, engineering, and math (STEM) careers. Industry, as the largest employer category of those with STEM backgrounds, stands to benefit considerably from greater inclusion of women and underrepresented minorities in the workforce. However, nothing short of a game-changing environment must be created to harness the talent of those not fully represented in the STEM workforce. Advancing Diversity in the US Industrial Science and Engineering Workforce is the summary of a workshop held in May, 2012 by the National Academy of Engineering, focusing on the needs and challenges facing industry in particular, and it is intended to facilitate further discussion and actions to address these complex issues. The workshop provided a forum for leaders from industry, academia, and professional associations to share best practices and innovative approaches to recruiting, retaining, and advancing women and underrepresented minorities in the scientific and engineering workforce throughout the nation's industries.
Keywords: Industry and Labor; Engineering and Technology

Understanding the Educational and Career Pathways of Engineers - National Academy of Engineering (The National Academies Press, 2018)
Engineering skills and knowledge are foundational to technological innovation and development that drive long-term economic growth and help solve societal challenges. Therefore, to ensure national competitiveness and quality of life it is important to understand and to continuously adapt and improve the educational and career pathways of engineers in the United States. To gather this understanding it is necessary to study the people with the engineering skills and knowledge as well as the evolving system of institutions, policies, markets, people, and other resources that together prepare, deploy, and replenish the nation's engineering workforce. This report explores the characteristics and career choices of engineering graduates, particularly those with a BS or MS degree, who constitute the vast majority of degreed engineers, as well as the characteristics of those with non-engineering degrees who are employed as engineers in the United States. It provides insight into their educational and career pathways and related decision making, the forces that influence their decisions, and the implications for major elements of engineering education-to-workforce pathways.
Keywords: Engineering and Technology

Engineering Studies at Tribal Colleges and Universities - National Academy of Engineering (The National Academies Press, 2006)
Keywords: Education; Engineering and Technology

Interim Report on Causes of the Deepwater Horizon Oil Rig Blowout and Ways to Prevent Such Events - National Academy of Engineering; National Research Council (The National Academies Press, 2010)
The National Academy of Engineering and the National Research Council have released the interim report of the Committee on the Analysis of Causes of the Deepwater Horizon Explosion, Fire, and Oil Spill to Identify Measures to Prevent Similar Accidents in the Future. The interim report includes the committee's preliminary findings and observations on various actions and decisions including well design, cementing operations, well monitoring, and well control actions. The interim report also considers management, oversight, and regulation of offshore operations. At the request of the U.S. Department of the Interior, the National Academy of Engineering/National Research Council (NAE/NRC) committee is examining the probable causes of the Deepwater Horizon explosion, fire, and oil spill in order to identify measures for preventing similar harm in the future. The study is organized under the auspices of the NAE and the NRC's Transportation Research Board, through its Marine Board, and the Division on Earth and Life Studies, with assistance from the Division on Engineering and Physical Sciences. The study will address the performance of technologies and practices involved in the probable causes of the Macondo well blowout and explosion on the Deepwater Horizon. It will also identify and recommend available technology, industry best practices, best available standards, and other measures in use around the world in deepwater exploratory drilling and well completion to avoid future occurrence of such events. The full scope and schedule for this project are available on our Current Projects Web site. The study does not address any issues associated with the subsequent fire and release of oil and gas into the Gulf of Mexico, such as the rescue and fire response, plans for the spill response, spill response and clean up, or the related consequences of the oil spill on the environment or human health. An NAE website provides information about this study and links to information about committee meetings and the composition of the committee. After meetings are held, information presented to the committee is posted on the site. The site also provides an opportunity for public comment on the topics of the study.
Keywords: Engineering and Technology; Environment and Environmental Studies